1988
DOI: 10.1016/0093-691x(88)90185-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of porcine plasma follitropin levels during superovulation treatment in cows

Abstract: Porcine follicle stimulating hormone (pFSH) and porcine luteinizing hormone (pLH), are widely used to induce superovulation in cows. An advantage of this treatment is that the LH:FSH ratio can be varied to optimize the growth of the ovarian follicles. However, due to the relatively short half-life of FSH, the superovulatory treatment requires numerous injections. A performant radioimmunoassay system (sensitivity=0.2 ng/ml plasma) was used to determine plasma pFSH levels in cows that were superovulated with 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
9

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 21 publications
0
21
0
9
Order By: Relevance
“…Debido a la media vida corta de la fsh (aproximadamente 5 a 12 horas), es preciso realizar múltiples aplicaciones intramusculares para conseguir el efecto de superovulación en las hembras bovinas [9,13]. Por tanto, los protocolos más comunes requieren seis a ocho aplicaciones de fsh con intervalos de doce horas, a fin de que varios folículos se desarrollen y pueda ocurrir una ovulación múltiple, para permitir mayor obtención de embriones en la colecta [14].…”
Section: Hormonas Utilizadas Para Superovulaciónunclassified
“…Debido a la media vida corta de la fsh (aproximadamente 5 a 12 horas), es preciso realizar múltiples aplicaciones intramusculares para conseguir el efecto de superovulación en las hembras bovinas [9,13]. Por tanto, los protocolos más comunes requieren seis a ocho aplicaciones de fsh con intervalos de doce horas, a fin de que varios folículos se desarrollen y pueda ocurrir una ovulación múltiple, para permitir mayor obtención de embriones en la colecta [14].…”
Section: Hormonas Utilizadas Para Superovulaciónunclassified
“…Each cow was given epidural anaesthesia using 60 mg Adocain (Lidokain HCL, 20mg/ml, Sanovel, Turkey) prior to flushing. The vulva was scrubbed with disinfectant and Foley catheter (14)(15)(16) FR, Agtech, USA) with a 15 ml bulb, inserted through the vagina and the cervix. A stainless steel stylet was used to stiffen the catheter to allow passage through the cervix and both horns were flushed with flushing media (990 ml ringer lactate+10 ml calf serum) using folley cathater inserted next to the utero-tubal junction.…”
Section: Methodsmentioning
confidence: 99%
“…FSH treatments have been more commonly used for superovulation (36,40). However, the biological half-life of FSH in cows has been reported relatively short (5 h or less) (15), thus it needs to be given frequently, in order to achieve high ovulation rates (32). It has been shown that twice daily injections of FSH with decreasing doses induce a greater superovulatory response than single injection daily treatments (32,44).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La FSH es eliminada rápidamente de la circulación (16), razón por la cual requiere su administración frecuente con la finalidad de mantener concentraciones en sangre suficientes para lograr una respuesta ovárica. Debe ser administrada mediante regímenes de inyecciones múltiples, generalmente de dosis decrecientes, que pueden resultar estresantes para los animales (17,18), laboriosos desde el punto de vista técnico (18) y conllevar a errores en la dosificación y en los tiempos de inyección (19), razones por las cuales son desventajosos.…”
Section: Introductionunclassified